On the rate of convergence of methods of projection-iterative type for Fredholm equations with periodic analytic kernels - Askarov, M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Optimal rates of convergence of projection-iterative methods and methods of Sokolov type are found for a certain class of Fredholm equations with analytic kernels that appear within the framework of the method of boundary integral equations.